2017
DOI: 10.1056/nejmoa1608889
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Minocycline in a Clinically Isolated Syndrome of Multiple Sclerosis

Abstract: The risk of conversion from a clinically isolated syndrome to multiple sclerosis was significantly lower with minocycline than with placebo over 6 months but not over 24 months. (Funded by the Multiple Sclerosis Society of Canada; ClinicalTrials.gov number, NCT00666887 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 20 publications
2
124
0
4
Order By: Relevance
“…In addition, to minimize the recall bias, we recruited only incidence cases. Although the validity of self-reported data on antibiotic use was not fully acknowledged, we also gathered further information, that is, the name and indication of consumed antibiotics to decrease the likelihood of major measurement errors Although the new Minocycline data have supported the benefit of antibiotics in delaying the clinically definite MS development, 35 the possibility of reverse causation is an issue threatening the validity of estimated ORs for antibiotic consumption. The index date in this study were the time of MS diagnosis rather than the time of the first symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to minimize the recall bias, we recruited only incidence cases. Although the validity of self-reported data on antibiotic use was not fully acknowledged, we also gathered further information, that is, the name and indication of consumed antibiotics to decrease the likelihood of major measurement errors Although the new Minocycline data have supported the benefit of antibiotics in delaying the clinically definite MS development, 35 the possibility of reverse causation is an issue threatening the validity of estimated ORs for antibiotic consumption. The index date in this study were the time of MS diagnosis rather than the time of the first symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, one example of translation of the knowledge on the role of MMPs in MS. Minocycline, a tetracycline antibiotic that exerts broad-spectrum inhibition of MMPs, demonstrated in two phase 2 studies in MS efficacy in reducing gadolinium-enhancing lesions [215,216], which encouraged the study group to execute a phase 3 clinical trial [217] with 142 patients with a first MS attack. Clinical and MRI findings suggested that minocycline in comparison to placebo reduced the risk for patients after a first attack to reach the criteria for formal MS diagnosis within 6 months by 28% (p = 0.006).…”
Section: Mmp Inhibitors As Treatment Options For Msmentioning
confidence: 99%
“…Alternative models are currently available, which involve different animal strains and species and different immune mechanisms, which will have to be analyzed in detail in future studies, despite of being more complex and difficult to handle.Active demyelination and neurodegeneration in multiple sclerosis and in autoimmune encephalomyelitis is invariably associated with the presence of activated macrophages and/or microglia (Brück et al, ; Ferguson et al, ) and blockade of macrophage function has been suggested as a therapeutic strategy for inflammatory brain diseases. So far, however, selective blockade of macrophage and microglia activation has not been established in multiple sclerosis treatment with the exception of a single phase II clinical trial, which showed a moderate beneficial effect of minocycline (Metz et al, ). To develop such a therapeutic strategy for MS patients, efficacy and safety have to be demonstrated in a broad spectrum of experimental models.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%